Appendiceal sarcoidosis presenting as acute appendicitis. Issue 3 (2nd July 2020) - Pendela, Venkata Satish; Munoz, Anisleidys; Chhabria, Mamta; Kudaravalli, Pujitha; Soliman, Megan; Soliman, Youssef
Abstract: Sarcoidosis is a chronic inflammatory multisystem disease. The stomach is the most commonly involved gastrointestinal organ. Symptomatic appendicular sarcoidosis is extremely rare. We present a case of a 49-year-old woman with abdominal pain. An ultrasound of the abdomen was suggestive of acute appendicitis. Laparoscopic appendectomy was performed and the pathology revealed nonnecrotizing granulomas. Biopsy of the mediastinal lymph nodes suggested noncaseating granulomas. She was treated with steroid therapy followed by mycophenolate mofetil. Our case demonstrates the importance of considering appendiceal sarcoid among the differentials in a patient with systemic sarcoidosis presenting with an acute abdomen.